Biological Properties and the Role of IL-25 in Disease Pathogenesis - Yuwan Liu; Zewei Shao; Guoqiang Shangguan; Qingli Bie; Bin Zhang (Journal of Immunology Research)
The interleukin- (IL-) 17 superfamily, a T cell-derived cytokine, consists of 6 ligands (IL-17A–IL-17F) and 5 receptors (IL-17RA–IL-17RE). IL-17A, a prototype member of this family, is involved in the pathogenesis of allergies, autoimmune diseases, allograft transplantations, and malignancies. By contrast, IL-17B is reported to be closely related to certain diseases, particularly tumors such as breast cancer, gastric cancer, and pancreatic cancer. Recently, the biological function of IL-17E (also called IL-25) in disease, particularly airway diseases, has attracted the attention of researchers. However, studies on IL-25 are scant. In this review, we detail the structural characteristics, expression patterns, responder cells, biological properties, and role of IL-25 in disease pathogenesis.